Collins Aikman Plastics Operations File for Creditor Protection Under CCAA; Action Taken in Conjunction with U.S. Chapter 11 Restructuring Process; Operations Continue Without Interruption (PR Newswire, 2007)
SOUTHFIELD, Mich., July 19 /PRNewswire-FirstCall/ -- Collins & AikmanCorporation ("Collins & Aikman") announced today that Collins & AikmanAutomotive Canada Inc. applied for creditor protection under the Companies'Creditors Arrangement Act (Canada) ("CCAA") in the Ontario Superior Court ofJustice. The CCAA filing for Collins & Aikman's Canadian Plastics operationsis a necessary step in completing its restructuring efforts. Certain of the foregoing statements constitute "forward-looking" statements, as that term is defined by the federal securities laws. You can find many of these statements by looking for words such as "may," "will," "expect," "anticipate," "believe," "estimate," "should," "continue," "predict," "preliminary," "potential" and similar words used herein. These forward-looking statements are intended to be subject to the safe harbor protection provided by the federal securities laws. These forward-looking statements are subject to numerous assumptions, risks and uncertainties. Because the statements are subject to risks and uncertainties, actual developments and results may differ materially from those expressed or implied by the forward-looking statements. Readers are cautioned not to place undue reliance on the statements, which speak only as of the date hereof. Additionally, the letter of intent identified in this press release is nonbinding and subject to numerous conditions such as completion of due diligence and negotiation of a definitive agreement.